Estudo da hidrodinâmica de um novo separador líquido-líquido: aplicação ao sistema óleo-bruto/água produzida - Moraes, Norberto Araújo de (2005)
This work aims to use a different hydrodynamic condition applied to a new design of mixer-settler on treating wastewater produced by petroleum industry, called MDIF (Misturador-Decantador à Inversão de Fases/ Mixer-Settler based on Phase Inversion MSPI). The use of this different hydrodynamic behaviour is possible due to vertical disposition of the device and the principle of Phase Inversion that controls the MDIF, providing the generation (creation) of a cascade of drops, into an organic layer, that works as micro-decanters, thus making possible the formation of a bed of non-coalesced drops, called Bed Formation . The use of this new hydrodynamics condition allows to increase the residence time of the oil carrier drops, into an organic layer, and the device can treat a greater volume of wastewater. In view of to get this condition it is necessary to operate at high throughput (58,6 m3.m-2.h-1). By results, the condition of Bed Formation is the best one to be used when MSPI operates with throughput up to 58,6 m3.m-2.h-1. The results using the condition of Bed Formation show that increasing the height of the bed of non-coalesced drops and/or decreasing the volumetric ratio (O/A) an increase of the separation efficiency is detected